Glutamate Modulation Synergizes With Anti-PD-1 Immunotherapy in Glioblastoma. (16th November 2020) - Medikonda, Ravi; Choi, John; Pant, Ayush; Saleh, Laura; Routkevitch, Denis; Tong, Luqing; Belcaid, Zineb; Kim, Young H; Jackson, Christopher M; Mathios, Dimitrios; Shah, Pavan P; Lim, Michael
Abstract: INTRODUCTION: Immune checkpoint inhibitors such as anti-PD-1 have shown promise in other cancers such as melanoma, but results in GBM have been disappointing thus far. It has been suggested that GBM has multiple mechanisms of immunosuppression, indicating a need for combinatorial treatment strategies. It is well understood that GBM increases glutamate in the tumor microenvironment, however the significance of this is not well-understood. METHODS: C57BL/6J mice were intracranially implanted with the GL261-Luc+ glioma cell line. Mice were randomized to control, anti-PD-1, BHV-4157, or combination anti-PD-1 and BHV-4157 treatment arms, and median overall survival was assessed. In vivo microdialysis was performed at the tumor site with administration of BHV-4157. Intratumoral immune cell populations were characterized by immunofluorescence and flow cytometry. RESULTS: BHV-4157 improved survival compared to control ( P  < .0001). In vivo microdialysis demonstrated glutamate concentration in the TME significantly decreased after BHV-4157 administration. Immunofluorescence and flow cytometry demonstrated increased CD4+ T cells and decreased FoxP3+ T cells with BHV-4157 treatment. When CD4+ or CD8+ T cells were depleted in mice prior to BHV-4157 administration, no survival benefit was observed ( P  < .05). CONCLUSION: In this study, we show synergy between anti-PD-1 immunotherapy and glutamate modulation. We provide a possible mechanism for this synergistic benefit by showing that BHV-4157 relies on CD4+ and CD8+ T cells. Our study sheds light on the role of excess glutamate in GBM and provides a basis for exploring further combinatorial approaches in this disease.